On-Field Removal of Large Anti-Concussive Football Helmets Using Current Guidelines Leads to Increased Passive Cervical Lordosis. Issue 7 (29th July 2019) - Warth, Ryan J.; Hays, Matthew R.; Dodd, Cameron T.; Rao, Mayank; Kumaravel, Manickam; Lowe, Walter R.; Prasarn, Mark L.
Objectives: Recent emphasis has been placed on concussion safety in American football and has driven the development of new anti-concussive helmet designs which are becoming more popular in the National Football League (NFL). However, their larger diameter may inadvertently complicate on-field stabilization procedures for players with suspected cervical spine injuries. The purpose of this study was to compare the total arc of extension in the supine position before and after removal of a traditional helmet and a larger-diameter anti-concussive helmet. We hypothesized that removal of the larger helmet would result in a significantly increased total arc of extension when compared to removal of a traditional helmet. Methods: IRB approval was obtained prior to initiation of this study. Following the guidance of a priori power analysis, 27 adult male volunteers between 20 and 30 years of age were enrolled. Head circumference, height, and weight measurements were obtained before being fitted with NFL-style shoulder pads, a traditional helmet (TH), and a newly-introduced, larger anti-concussive helmet (LH). With the shoulder pads in place, each subject was asked to lay supine on the x-ray table which was equipped with standardized visible landmarks to facilitate consistent positioning between patients. Lateral radiographs were then obtained while wearing the TH, the LH, and while wearing no helmet (NH). With assistance, subjects were immobilized to the extent possible while removing/exchanging headgear between radiographs. Three cobb angle measurements were obtained for each helmet condition beginning from the most caudal aspect of C1 to the most cranial aspects of the C3, C4, and C5 vertebral bodies, respectively. Maintenance of atlanto-dens intervals were confirmed between helmet conditions in each subject. All Cobb angles were measured in duplicate by two independent observers on two occasions separated by at least 2 weeks for calculation of inter- and intra-rater reliability (κ). Statistical comparisons between helmet conditions were performed using repeated measures analysis of variance (ANOVA). Statistical significance was declared when p<0.05. Results: Twenty-seven male subjects with a mean age of 24.0 years (range, 22.0-36.0 years; standard deviation [SD], 3.0 years), mean body mass index (BMI) of 25.1 kg/m2 (range, 21.0-31.9 kg/m2; SD, 2.7 kg/m2), and mean head circumference of 58.2 cm (range, 53.0-62.0 cm; SD, 1.6 cm). Cobb angle measurements were found to have good-to-excellent intra-class correlation (κ). Relative to NH, the average total extension arc after removal LH removal was significantly greater than after SH removal between the C1-C3 (-2.6°; p=0.024), C1-C4 (-2.6°; p=0.036), and C1-C5 intervals (-2.9°; p=0.023), amounting to a 50-60% increased arc of cervical extension after removal of the LH relative to the TH (Table 1 and Figure 1). Conclusion: The degree of passive cervical lordosis that occurs after removal of new larger-diameter anti-concussive football helmets in the supine position is significantly greater than after removal of traditional helmets, thus potentially increasing the risk of iatrogenic cervical spine injury while attempting on-field helmet removal. Current guidelines and procedures for management of on-field cervical spine trauma in American football should be modified to account for larger helmet designs that are becoming more popular in American football. Table 1. Average Cobb angle measurements between each helmet condition No Helmet (NH) a Larger Helmet (LH) a Traditional Helmet (TH) a P-Values (LH versus TH) C1-C3 24.0° (1.8°) 16.4° (1.6°) 19.0° (1.4°) 0.024* C1-C4 25.7° (2.0°) 18.0° (1.7°) 20.5° (1.6°) 0.036* C1-C5 27.2° (2.0°) 19.2° (1.8°) 22.1° (1.6°) 0.023* a 95% Confidence Intervals in parentheses.